2017
DOI: 10.1111/iju.13356
|View full text |Cite
|
Sign up to set email alerts
|

Substitution urethroplasty using oral mucosa graft for male anterior urethral stricture disease: Current topics and reviews

Abstract: Male anterior urethral stricture is scarring of the subepithelial tissue of the corpus spongiosum that constricts the urethral lumen, decreasing the urinary stream. Its surgical management is a challenging problem, and has changed dramatically in the past several decades. Open surgical repair using grafts or flaps, called substitution urethroplasty, has become the gold standard procedure for anterior urethral strictures that are not amenable to excision and primary anastomosis. Oral mucosa harvested from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 74 publications
2
52
0
4
Order By: Relevance
“…3 My opinion is that lingual mucosa is better in patients with a short stricture requiring only a small amount of graft, in patients with a lengthy stricture requiring additional tissue grafts other than buccal mucosa and in patients undergoing salvage urethroplasty whose buccal mucosa has already been bilaterally harvested. 4 In contrast to my opinion, Aldaqadossi et al 5 showed various advantages of lingual mucosa, and reported their experience in one-stage onlay augmentation repair of LS-related anterior urethral stricture using a lingual mucosa graft in 36 patients with a long-term postoperative follow-up period (median 66.5 months) and a high success rate of 88.2%, which is comparable to that in previous series using buccal mucosa. 1 The authors were able to harvest a sufficient graft size (median length 8.5 cm, median width 1.8 cm) for the reconstruction of LS-related urethral strictures with low to no long-term donor site morbidity.…”
Section: Editorial Commentmentioning
confidence: 69%
See 1 more Smart Citation
“…3 My opinion is that lingual mucosa is better in patients with a short stricture requiring only a small amount of graft, in patients with a lengthy stricture requiring additional tissue grafts other than buccal mucosa and in patients undergoing salvage urethroplasty whose buccal mucosa has already been bilaterally harvested. 4 In contrast to my opinion, Aldaqadossi et al 5 showed various advantages of lingual mucosa, and reported their experience in one-stage onlay augmentation repair of LS-related anterior urethral stricture using a lingual mucosa graft in 36 patients with a long-term postoperative follow-up period (median 66.5 months) and a high success rate of 88.2%, which is comparable to that in previous series using buccal mucosa. 1 The authors were able to harvest a sufficient graft size (median length 8.5 cm, median width 1.8 cm) for the reconstruction of LS-related urethral strictures with low to no long-term donor site morbidity.…”
Section: Editorial Commentmentioning
confidence: 69%
“…Although which graft to use depends on the surgeon’s preference, buccal mucosa seems to be preferred, because lingual mucosa is typically not as wide and is more flimsy . My opinion is that lingual mucosa is better in patients with a short stricture requiring only a small amount of graft, in patients with a lengthy stricture requiring additional tissue grafts other than buccal mucosa and in patients undergoing salvage urethroplasty whose buccal mucosa has already been bilaterally harvested . In contrast to my opinion, Aldaqadossi et al.…”
mentioning
confidence: 88%
“…In order to prevent hematoma formation and to achieve secure graft intake, we placed dressing materials untouched for 7 days, which is longer than that in conventional staged BMG urethroplasty (5 days). This case needed wide and circumferential repair of the urethra, so we used two‐stage urethroplasty with BMG . If the intraoperative tumoral margin had been positive, we would have performed partial penectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the healing process, such a bridging graft can pull both anastomotic ends, even when the graft itself shrinks. The clinical trial did not treat penile urethral reconstruction, where substitution is definitively required . Therefore, the trial of a tissue‐engineered urethra could not be judged as a clear success until further study is reported in patients truly in need of them.…”
Section: Human Clinical Trialsmentioning
confidence: 99%